Career Interest and Readiness among Grade 10 Students of A Private University in Cebu City - Boctot, Jenalyn B.; Cabatingan, Alicia P; Polinar, Mark Anthony N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This descriptive-correlational study aimed to identify the students’ awareness regarding their career interests and career readiness regarding the learning experience, learning outcomes, and pre-college experience of Grade 10 students at a private university in Cebu City. Using Slovin’s formula, there should be 206 respondents; however, 198 have participated. Also, several statistical treatments were applied to the study’s findings. The findings regarding the profile and the career interests of the students, as well as their age, gender, total income, parents' educational attainment, and occupation, found no relationship. Another finding regarding the profile and career readiness revealed that both the mother and father's age and educational attainment have a significant relationship. Career interest and career readiness have a solid positive relationship. Thus, the finding shows that the relationship between the two variables is solid, and it also indicates that interest will influence the student's career readiness and how ready they are to step up to the next level of their studies. The findings disclosed that the student's career interest is a significant factor (computed value 14.4) in pursuing their major field of specialization, primarily supported by their career readiness. The more the student is interested in a particular field, the more the student is ready to pursue his dream career. Based on the findings and conclusion, it is suggested that all grade levels should be given a career interest survey and ready to think, prepare, and choose what career path they need to take in the future. As much as possible, parents should also play a significant role in selecting the students' careers so that they can guide their students in what career is best suited for them.